Are Johannesburg peri-central neighbourhoods irremediably ‘fluid’? The local governance of diversity, mobility and competition in Yeoville & Bertrams - Benit-Gbaffou, Claire (Wits University Press, 2014)
Johannesburg’s inner city, often emblematized by the infamously known Hillbrow, has often constituted the point of departure for depicting urban chaos, unpredictability, endless mobility, fluidity and undecipherable change – be it in novels and movies (see 2002 Welcome to our Hillbrow, 2010 Zoo City, 2008 Jerusalema), or in academic literature (Morris 1999, Simone 2006). Inner city neighbourhoods, in the CBD but also at its immediate fringe (‘peri-central’ areas) are currently functioning as ports of entry into South African economic capital, for both national and international migrants. They are characterized by a degree of urban decay that have earned these neighborhoods the label of ‘slums’, ‘sinkholes’, in need of ‘urban management’ and re-affirmation of ‘law and order’. Some have also attracted specific attempts at urban regeneration led mostly by the municipality, followed or not by private investment. They are all marked by a level of informality (in housing and in economic activities) which is often a condition for low-income migrants to enter the urban labour and housing markets.
Fragmentation of civil society structures; contradictory and shifting facets of the city; power inequality
Keywords: Hillbrow; Low-income migrants; Johannesburg inner city; urban chaos; urban fluidity; urban regeneration; Yeoville; Bertrams; Johannesburg peri-central neighbourhoods